From poetry out loud to thinking out loud: The ESL students' experience / Sharina Saad ... [et al.] - Saad, Sharina; Amat, Rafidah; Nordin, Razanawati; Hasan, Asrol; Zolkifli, Alia Nabella Fateha (Research Management Centre (RMC), 2023)
Public speaking apprehension can detrimentally affect academic performance, attendance, participation, and motivation. This study investigates into the formidable challenge of public speaking anxiety (PSA) among students during oral presentations and proposes an innovative solution through the utilisation of Poetry Out Loud activities. Two interventions were executed with ESL learners and the researchers used qualitative methods to deduce the result. The initial phase involved the collective reading of a poetry compilation, fostering a shared experience. Subsequently, students engaged with the "Hello Poetry" website, selecting and practicing poems in pairs to refine expressive delivery. The culmination consisted of creative video presentations of their chosen poems. Once the completed the activities, they were given an open-ended survey. The study uncovers that Poetry Out Loud activities positively influence students' speaking skills. These findings underscore the efficacy of communal poem reading and interactive recitation in bolstering confidence, oral proficiency, and reading fluency. Implications point toward the importance of innovative strategies to mitigate PSA-related challenges and nurture essential public speaking aptitudes.